2004
DOI: 10.1088/0029-5515/44/4/005
|View full text |Cite
|
Sign up to set email alerts
|

Confinement studies of auxiliary heated NSTX plasmas

Abstract: Abstract:The confinement of auxiliary heated NSTX discharges is discussed. The energy confinement time in plasmas with either L-mode or H-mode edges is enhanced over the values given by the ITER97L and ITER98Pby(2) scalings, being up to 2-3 times L-mode and 1.5 times H-mode. TRANSP calculations based on the kinetic profile measurements reproduce the magnetics-based determination of stored energy and the measured neutron production rate. Power balance calculations reveal that, in a high power neutral beam heate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 31 publications
6
37
0
1
Order By: Relevance
“…Thus, as for high β T discharges in NSTX, low-n mode induced confinement degradation and rotation decay appear to be important factors in the disruption dynamics of high β P discharges. Prior to the onset of the abrupt drops in β P in Figure 13, the global energy confinement time for this 6MW discharge is 40-50ms with H-factor of 2-2.5 relative to ITER-89P scaling [31]. This confinement estimate ignores the 1 to 2MW loss of NBI heating power to prompt loss and charge exchange due to operating at reduced plasma current and low internal inductance.…”
Section: High β P Dischargesmentioning
confidence: 91%
“…Thus, as for high β T discharges in NSTX, low-n mode induced confinement degradation and rotation decay appear to be important factors in the disruption dynamics of high β P discharges. Prior to the onset of the abrupt drops in β P in Figure 13, the global energy confinement time for this 6MW discharge is 40-50ms with H-factor of 2-2.5 relative to ITER-89P scaling [31]. This confinement estimate ignores the 1 to 2MW loss of NBI heating power to prompt loss and charge exchange due to operating at reduced plasma current and low internal inductance.…”
Section: High β P Dischargesmentioning
confidence: 91%
“…As seen in Figure 6, the improvement in global electron confinement with increasing lithium deposition is reflected in a reduction in the electron thermal diffusivity calculated by TRANSP [18] using the measured profiles of the temperatures and density and assuming classical thermalization of the neutral beam heating.…”
Section: Lithium Coating Techniques and Their Effects In Nstxmentioning
confidence: 97%
“…6 Local transport analyses of the MAST discharges indicated that the ion thermal transport was close to the neoclassical level, 7 consistent with early results on NSTX as well. 8 Microinstability analyses with linear gyrokinetic codes indicated that the ExB shearing rates in MAST were sufficiently high as to suppress long-wavelength Ion Temperature Gradient (ITG) turbulence. The source of the anomalous electron transport was believed to be either microtearing modes in the core, or radial streamers associated with saturated Electron Temperature Gradient (ETG) turbulence 7,9 .…”
Section: Introductionmentioning
confidence: 99%